PERTANGGUNGJAWABAN PIDANA ANAK SEBAGAI PELAKU TINDAK PIDANA TERORISME DI INDONESIA - GAUTAMA, PUTU GITHA CAESARA; Yudiantara, I Gusti Ngurah Nyoman Krisnadi (Kertha Negara : Journal Ilmu Hukum; Vol 11 No 11 (2023), 2024)
The aim of writing the article is to find answers to questions regarding the criminal responsibility of children as perpetrators of terrorism in Indonesia and what the government's efforts are to prevent children from falling into criminal acts of terrorism. The research method applied is normative research, centered on the analysis of written legal documents such as laws, court decisions and legal expert opinions using the statute approach. The results show that children's criminal responsibility for terrorism cases is based on the SPPA Law. In the SPPA Law, Article 81 states "the prison sentence that can be imposed on minors is a maximum of ½ (one-half) of the maximum penalty of imprisonment for adults." and "if the criminal offense committed by the child is a criminal offense punishable by the death penalty or life imprisonment, the penalty imposed is a maximum imprisonment of 10 (ten) years." The government has also carried out preventive efforts as mandated by Article 43A paragraph (1) of the PTPT Law, which is carried out in 3 ways, namely national preparedness, counter-radicalization and de-radicalization. Furthermore, prevention of children is also carried out through PERMEN PPPA No. 7/2019 in primary, secondary and tertiary forms.